PEMBERDAYAAN PEREMPUAN KAMPUNG SAMPORA KELURAHAN CIBINONG DALAM PENGELOLAAN SAMPAH RUMAH - Enok Rusmanah; Haqi Fadillah; Dwi Meyliani Riswanti (Universitas Serang Raya, 2021)
Waste and its management are still a common problem. It is estimated that 175,000 tonnes of waste are generated in a day and most of this waste comes from households. Various efforts have been held to address the problem, including the movement to sort waste from home. Community based waste management programs also have been launched including My Bogor Regency Green and Clean which aimed to create environmentaly friendly village (KRL). However, in Sampora Village, Cibinong, Bogor Regency, waste is still a serious problem. KRL was not operated optimally. Garbages were still dumped into the rivers and the road. People are lack of understanding on how to manage and utilize waste, equipment and waste bank. Therefore, knowledge, training, and assistance in waste management are necessity. In line with the program of sorting waste from home, the activities involve empowering of housewives as people who do most of their activities at home. The method used for this activities were sharing knowledge on how to sort household waste, managing waste with 3R (Reuse, Reduce, Recycle) and maximizing a waste bank. Further, a composter was also prepared to compost organic waste. The results are housewives felt more knowledgeable and willing to sort waste from home.